Bibliography for Coroplastic Topics 2019-2020 - Association for Coroplastic Studies (Les Carnets de l’ACoSt)
The following is a compilation of publications on coroplastic topics for 2019-2020. As this is taken from Dyabola, all reference Greek or Roman terracottas. Bibliography on coroplastic topics that focus on other areas of the ancient world are very much appreciated and can be sent to uhlenbrj@hawkmail.newpaltz.edu.